Assessing the Level of Project Management Maturity in Real Estate Development Companies in Nepal - Makaju, Ankita (My University, 2026)
This study is aimed at assessing the level of project management maturity of real estate development companies in Nepal. Real estate sector in Nepal has increasingly been facing problems related to delays in project schedule, overruns of cost and issues with quality. So, for improving project outcomes it is necessary to understand the current levels of project management maturity in real estate development companies in Nepal. Despite these problems there are few empirical contributions regarding organizational maturity in real estate sector. Thus, to address this gap this research is focused on evaluating companies’ maturity level based on the ten domains of project management body of knowledge areas according to PMBOK. These ten knowledge areas offer an extensive way to identify the organizational key strengths and areas for improvement of the project. This research was conducted using the quantitative research approach. Using structured Likert-scale questionnaires, primary data was collected from professionals such as project managers, engineers and senior management personnel from eight real estate companies. Geographically, the research primarily covers real estate development activities in major urban areas of Nepal like Kathmandu, Lalitpur, Pokhara and Chitwan where real estate development is concentrated. PMMM was selected for this study among other alternatives such as CMMI, OPM3, K-PMMM and P3M3. A five level maturity model adapted from established PMMM has been used to evaluate organizational maturity. The data acquired from the Likert-scale survey questionnaire were analysed using the software named Jeffreys’s Amazing Statistics Program (JASP). For the statistical analysis the mean for specific knowledge areas were calculated by averaging the mean scores of ten domains of knowledge areas according to PMBOK. Then the standard deviation was calculated to understand the variability or the consistency of the respondents' answers. To confirm the reliability of this research the reliability test was conducted using Cronbach’s alpha. The findings from the data analysis have revealed the achieved score of 3.44 indicating that the real estate construction companies of Nepal are at the upper end of Level 3 which is ‘Defined'. This means real estate companies in Nepal have generally established standardized project management processes that are documented and followed across most projects. However, the score is still significantly below Level 4 quantitatively managed. So, the recommendations have been made for the improvement of risk management procedures, the introduction of formal scope change control, and for the development of sector specific project management guidance. This research is beneficial for academic literature as well as construction sector. It offers practical survey insights to policymakers that support their project to achieve more predictable and sustainable project outcomes.
Keywords: project management; Strategic Project Management; Master’s Programme in Industrial Engineering and Management